An Update on Voriconazole in Ophthalmology - Mallikarjun M Heralgi; Ajay Badami; Hariprasad Vokuda; Kavitha Venkatachalam (Delhi Journal of Ophthalmology)
Ocular mycosis is one of the leading causes of corneal blindness. The range of common antifungal agents available for ocular mycosis remains inadequate and is generally associated with poor clinical outcomes. Voriconazole is a newer generation triazole antifungal agent, only marketed in systemic formulation, with broad-spectrum activity and a high intraocular penetration. Voriconazole has demonstrated effectiveness against ocular mycosis. This review article is aimed at providing comprehensive information about the uses of voriconazole in ophthalmology in different scenarios. Off label preparation and different routes of administration like intrastromal, intracameral and intravitreal etc. been described along with case reports and relevant studies. It has been demonstrated in many case reports that voriconazole has been used as a stand alone therapy, as a second line of drug in unresponsive cases and also as an adjunctive drug along with other antifungals.